Phase transformation study of Iraqi Bentonite with Al2O3 and MgO as additions at high temperatures (Baghdad Science Journal, 2012)
Iraqi bentonite is used as main material for preparing ceramic samples with the additions of alumina and magnesia. X-ray diffractions analyses were carried out for the raw material at room temperature. The sequence of mineral phase's transformations of the bentonite for temperatures 1000 ,1100 ,1200 and 1250 ºC reflects that it finally transformed in to mullite 39.18% and cristobalite 62.82%. Samples of different weight constituent were prepared. The effect of its constitutional change reveals through its heat treatments at 1000,1100,1200,1250and 1300ºC .The samples of additions less than 15% of alumina and magnesia could not stand up to 1300ºC while the samples of addition more than 15% are stable .That is shown by analyzing of X-ray diffraction pattern after heat treatments of the samples. The growth of mineralogical phases like cordierite, anorthite ,mullite, cristobalite wollastonite with highest percentage ratio of anorthite 87.53%,cordirite77.35% and wallostonite 62.35% .So the presence refractory materials in the obtained samples highly support the possibility of using the bentonite with additions in the ceramics industry for high temperatures.